Pengaruh Kompetensi Profesional Guru dan Motivasi Kerja Terhadap Kinerja Guru Pada Sekolah Menengah Atas di Kabupaten Ciamis - Gani Kardani (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the effect of Teacher Professional Competence and Work Motivation on teacher performance in Senior High Schools in Ciamis Regency. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study the Professional Competence of Teachers has a significant effect on teacher performance by 51.1%, hypothesis testing obtained t count> t table or (9.480> 1.988). Work motivation has a significant effect on teacher performance by 37.3%, the hypothesis test is obtained t count> t table or (7.155> 1.988). Teacher Professional Competence and Work Motivation simultaneously have a significant effect on teacher performance with the regression equation Y = 8.189 + 0.492X1 + 0.304X2. The contribution of the effect was 57.4%, the hypothesis test obtained F count> F table or (54.372> 2.710).